Pemanfaatan Smartphone Sebagai Media Pembelajaran Berbasis Daring Bagi Peserta Didik SMA Pada Masa Pandemi Covid-19 - Khalida Juniarti; Corry Corry; Ulung Napitu (BEST Journal (Biology Education, Sains and Technology), 2022)
This study aims to examine the use of smartphones as online learning media for high school students during the covid-19 pandemic and to examine the obstacles faced by students in using smartphones as online learning media for high school students during the covid-19 pandemic. The data collection technique used by the researcher is literature study. Data analysis techniques in this study using qualitative analysis techniques by means of deduction. The results of the study show that smarphones are used as online learning media, namely used as a communication tool for students and as a tool to add insight. The obstacles faced by students in utilizing smartphones as online-based learning media are the lack of internet network access, high internet credit costs and authenticity of the assignments submitted by students